2018
DOI: 10.1038/s41467-018-07506-1
|View full text |Cite
|
Sign up to set email alerts
|

Cis interaction between sialylated FcγRIIA and the αI-domain of Mac-1 limits antibody-mediated neutrophil recruitment

Abstract: Vascular-deposited IgG immune complexes promote neutrophil recruitment, but how this process is regulated is still unclear. Here we show that the CD18 integrin Mac-1, in its bent state, interacts with the IgG receptor FcγRIIA in cis to reduce the affinity of FcγRIIA for IgG and inhibit FcγRIIA-mediated neutrophil recruitment under flow. The Mac-1 rs1143679 lupus-risk variant reverses Mac-1 inhibition of FcγRIIA, as does a Mac-1 ligand and a mutation in Mac-1’s ligand binding αI-domain. Sialylated complex glyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 67 publications
5
67
0
Order By: Relevance
“…An example here is the Ly49A binding to the H-2D d allele, most of which is undertaken is a cis-manner, controlling the number of receptors available for trans binding and the stability of the binding [66,67]. Interestingly, more recent studies by Saggu et al, have shown that the CD18 integrin, Mac-1, on the surface of neutrophils, is capable of cis-binding the FcγRIIA receptors, decreasing their affinity to IgG complexes and thus reducing the recruitment of neutrophils to the immune site [68]. Indeed, authors have demonstrated that silencing of CD18 in mice using siRNA or knocking out the corresponding gene leads to an accumulation of neutrophils in kidneys upon mice injection with a nephrotoxic serum [68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An example here is the Ly49A binding to the H-2D d allele, most of which is undertaken is a cis-manner, controlling the number of receptors available for trans binding and the stability of the binding [66,67]. Interestingly, more recent studies by Saggu et al, have shown that the CD18 integrin, Mac-1, on the surface of neutrophils, is capable of cis-binding the FcγRIIA receptors, decreasing their affinity to IgG complexes and thus reducing the recruitment of neutrophils to the immune site [68]. Indeed, authors have demonstrated that silencing of CD18 in mice using siRNA or knocking out the corresponding gene leads to an accumulation of neutrophils in kidneys upon mice injection with a nephrotoxic serum [68].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, more recent studies by Saggu et al, have shown that the CD18 integrin, Mac-1, on the surface of neutrophils, is capable of cis-binding the FcγRIIA receptors, decreasing their affinity to IgG complexes and thus reducing the recruitment of neutrophils to the immune site [68]. Indeed, authors have demonstrated that silencing of CD18 in mice using siRNA or knocking out the corresponding gene leads to an accumulation of neutrophils in kidneys upon mice injection with a nephrotoxic serum [68]. Thus, the cis-interaction of Mac-1 and FcγRIIA is a mean by which the immune system regulates neutrophil accumulation, and a disruption of such process could have significant implications in inflammatory and autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in human PMN FcγRIIIB is constitutively associated with MAC-1 [111]. Similarly, MAC-1 was reported to physically interact with FcγRIIA in human PMN and to amplify calcium-mediated signaling of FcγRIIA/B, which resulted in an enhanced phagocytosis and release of pro-inflammatory cytokines [112]. The authors suggested that binding of immune complexes to the FcR resulted in intracellular rearrangements which in turn conferred release of MAC-1 from the cytoskeletal network and allowed its transfer to the site of phagocytosis [113].…”
Section: Phagocytosismentioning
confidence: 99%
“…The cis interaction of β2 integrins with other ligands, such as FcγRIIA, was demonstrated by an independent study. 35 Based on our findings by flow cytometry, microscopy, and cell function (arrest, slow rolling, spreading), we conclude that the E − H + conformation is not affected by introducing the β2 TMD kink.…”
Section: Discussionmentioning
confidence: 51%